2012
DOI: 10.1063/1.3695349
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the runaway electron beam formed in a discharge in air at atmospheric pressure

Abstract: The discharge condition to enhance electron density of capacitively coupled plasma with multi-holed electrode Phys. Plasmas 19, 093508 (2012) Atomic gas temperature in a nonequilibrium high-intensity discharge lamp determined from the red wing of the resonance mercury line 254nm J. Appl. Phys. 112, 053304 (2012) Diagnostics development for quasi-steady-state operation of the Wendelstein 7-X stellarator (invited) Rev. Sci. Instrum. 83, 10D730 (2012) Experimental determination of dielectric barrier discharge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Before the discovery of X‐rays from lightning, it was not clear that such conditions exist in the atmosphere to allow the CRE to occur. Researchers have suggested that fields exceeding E c can be produced at streamer tips in association with lightning leaders [ Moss et al , ; Oreshkin et al , ]. In this scenario, the runaway electrons can be produced from the free low‐energy electron population and then gain just enough energy to continue their path through Wilson's runaway electron mechanism from the lower field region in front of the leaders.…”
Section: Theorymentioning
confidence: 99%
“…Before the discovery of X‐rays from lightning, it was not clear that such conditions exist in the atmosphere to allow the CRE to occur. Researchers have suggested that fields exceeding E c can be produced at streamer tips in association with lightning leaders [ Moss et al , ; Oreshkin et al , ]. In this scenario, the runaway electrons can be produced from the free low‐energy electron population and then gain just enough energy to continue their path through Wilson's runaway electron mechanism from the lower field region in front of the leaders.…”
Section: Theorymentioning
confidence: 99%
“…Each of the thresholds is approximately an order of magnitude larger than the previous one. It is legitimate to assume that thermal threshold may be exceeded in streamers' tips in sprites and lightnings (Moss et al, 2006) and in sparks at atmospheric pressure (Oreshkin et al, 2012).…”
Section: Figmentioning
confidence: 99%
“…In this case, a negative superficial charge is concentrated at the hemisphere surface which screens the external electric field. The number of electrons at the hemisphere surface (in the Debye layer) is given [14]…”
Section: Simulation Of the Evolution Of A Runaway Electron Beam In Highly Overvolted Gas Dischargesmentioning
confidence: 99%
“…where E ez is the electric field strength at the EZ surface. As conditions for runaway of electrons from the EZ surface are realized, electrons are injected with the current density [14] 2 / 3 23…”
Section: Simulation Of the Evolution Of A Runaway Electron Beam In Highly Overvolted Gas Dischargesmentioning
confidence: 99%